Prognostic impact of systemic immune inflammatory index in patients with reduced ejection fraction heart failure - Murat Özmen; Onur Altınkaya; İbrahim Saraç; Selim Aydemir; Sidar Şiyar Aydın; Faruk Aydınyılmaz; Emrah Aksakal (BMC Cardiovascular Disorders)
Abstract Background The systemic immune-inflammation index (SII), a novel marker derived from the combination of platelet, neutrophil, and lymphocyte counts, has been linked to unfavorable clinical outcomes in various malignancies and inflammatory conditions. This study aims to assess the association between SII and disease prognosis in patients with heart failure with reduced ejection fraction (HFrEF). Methods A total of 521 patients (72% male; mean age: 67 ± 13 years) diagnosed with HFrEF were retrospectively analyzed. Clinical, demographic, laboratory, and echocardiographic data were collected. SII scores were calculated for all patients, and their prognostic significance and clinical outcomes were evaluated. Results 521 patients were analyzed. According to current findings, all-cause mortality occurred in 87 patient during the follow-up period. The mean SII in the mortality group was higher than in the survivors and was found to be statistically significant. (878.57 vs. 643.65; p = 0.003, respectively) In the multivariable regression model SII was found to be an independent risk factor for mortality. (p = 0.031) The AUC of SII for mortality prediction was 0.602 (95% CI = 0.531–0.673), the cut-off value was 729, and the sensitivity and specificity were 59.3% and 59.6% (p = 0.003). Conclusion This study demonstrates a significant association between SII and both survival and prognosis in patients with HFrEF. Notably, the SII index was found to be an independent predictor of mortality in this patient population.